Sphingosine 1-Phosphate (S1P) Signaling in Glioblastoma Multiforme—A Systematic Review - Mahajan-Thakur, Shailaja (Int J Mol Sci, 2017)
The multifunctional sphingosine-1-phosphate (S1P) is a lipid signaling molecule and central regulator in the development of several cancer types. In recent years, intriguing information has become available regarding the role of S1P in the progression of Glioblastoma multiforme (GBM), the most aggressive and common brain tumor in adults. S1P modulates numerous cellular processes in GBM, such as oncogenesis, proliferation and survival, invasion, migration, metastasis and stem cell behavior. These processes are regulated via a family of five G-protein-coupled S1P receptors (S1PR1-5) and may involve mainly unknown intracellular targets. Distinct expression patterns and multiple intracellular signaling pathways of each S1PR subtype enable S1P to exert its pleiotropic cellular actions. Several studies have demonstrated alterations in S1P levels, the involvement of S1PRs and S1P metabolizing enzymes in GBM pathophysiology. While the tumorigenic actions of S1P involve the activation of several kinases and transcription factors, the specific G-protein (Gi, Gq, and G12/13)-coupled signaling pathways and downstream mediated effects in GBM remain to be elucidated in detail. This review summarizes the recent findings concerning the role of S1P and its receptors in GBM. We further highlight the current insights into the signaling pathways considered fundamental for regulating the cellular processes in GMB and ultimately patient prognosis.